Geoecologia das paisagens e agrofloresta: modelo para um desenvolvimento sustentável no semiárido cearense - Mota, Narciso Ferreira (2020)
The research of this thesis presents the socioeconomic and environmental feasibility of the Agroforestry Systems developed by family farmers in four areas of the semiarid Ceará, Sertão and littoral zone of the state, in the municipalities of Pindoretama, Trairí and Quixadá. The research on the sustainability of agroecosystems was intended to generate subsidies for the participatory elaboration of propositional models of Agroforestry Systems, with better productivity to contribute to food safety and sovereignty, in the income generation for families, and to preserve through use of the environment. To carry out this work, we used the information generated collectively by various rural and urban protagonists participating in Agroecology and Environmental Education projects performed by non-governmental organizations and by an extension group at the Federal University of Ceará, from 2007 to 2017. These data were produced by means of technical visits, planning meetings, interviews, questionnaires, mapping, courses, workshops, monitoring practical implementation actions and agroecological management of Agroforestry Systems (AFS’s). These data were analyzed, organized in graphs and tables, compared the conducting systems of the oldest AFS’s with the most recent ones, evaluating their food production, the income generated, the contributions to the environment were listed, and mainly registered the social developments arising from the families and communities working with Agroecology. Suggestions were obtained from the participants and with them elaborated propositional drawings of more adapted and resilient AFS’s, with better productivity, planned to supply the family with quality food, generate income, and conserve nature. These designs are intended to be a contribution to the construction of more sustainable agroecosystems to improve the quality of life of rural and urban communities which develop Agroecology.